RISE: UiTM's global effort in training young aspiring neuroscientists / Prof. Dr Abu Bakar Abdul Majeed - Abdul Majeed, Abu Bakar (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
The Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) had the privilege to host the IBRO-APRC Associate School of Neuroscience on 8th-14th AUgust, 2016 and 24th-30th September 2018.